2022
DOI: 10.7883/yoken.jjid.2021.139
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of CTX-M-55 in Extended-Sectrum β-Lactamase-Producing <i>Escherichia coli</i> from Vegetables Sold in Local Markets of Northern Thailand

Abstract: Extended-spectrum β-lactamase (ESBL)-producing Escherichia coli are spreading worldwide and pose a public health issue. An assessment of their presence in the environment and in food chain products would clarify the pathway of this foodborne transmission. Here, we investigated the prevalence of ESBL-producing E. coli in fresh vegetables purchased from fresh markets in Chiang Rai, Thailand. Overall, 8.8% of the samples collected contained ESBL-producing E. coli, of which 81.3% were multidrug-resistant. All isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Most E. coli observed in this study belong to the phylogroup B1 (46.5%), A (17.4%), and C (16.3%), in accordance with a previous study ( Chotinantakul, Woottisin & Okada, 2022 ). On the other hand, phylogroup A was the predominant type isolated from dairy farm wastewater in Chiang Mai ( Saekhow & Sriphannam, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Most E. coli observed in this study belong to the phylogroup B1 (46.5%), A (17.4%), and C (16.3%), in accordance with a previous study ( Chotinantakul, Woottisin & Okada, 2022 ). On the other hand, phylogroup A was the predominant type isolated from dairy farm wastewater in Chiang Mai ( Saekhow & Sriphannam, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with a previous study, related to E. coli isolated from patients in a tertiary care hospital in Phayao, which is close to Chiang Rai province ( Srimora et al, 2021 ). A study in ESBL-producing E. coli from vegetables in Chiang Rai demonstrated that most isolates were resistant to aztreonam, gentamicin and trimethoprim/sulfonamide ( Chotinantakul, Woottisin & Okada, 2022 ), while ESBL isolates in this work were occasionally resistant to gentamicin and trimethoprim/sulfonamide. Taken together, our data would suggest that river waters are likely to be the reservoir of MDR E. coli that could disseminate resistance genes over extensive areas.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…CTX-M-55 was first found in E. coli in Thailand in 2005 ( 15 ) and first detected in Salmonella in China in 2011 ( 21 ). Recently, the detection rate of CTX-M-55 identified in ESBLs E. coli has increased gradually worldwide, especially in China, irrespective of the clinic, livestock industry, and environment ( 22 29 ). In several studies ( 16 , 23 , 30 ), the detection rate of CTX-M-55 in E. coli has exceeded the rate of CTX-M-15, becoming the second prevalent ESBLs in China.…”
Section: Introductionmentioning
confidence: 99%
“…Z 1-α/2 = Standard normal variant at 5% type I error (P < 0.05); P = Expected prevalence of 4.0-10.12% was based on previous studies [7,21,[28][29][30][31][32][33]; d = Absolute error or precision (which is 5%). The expected minimum sample to be collected ranged from 59-140.…”
Section: Study Area and Sample Collectionmentioning
confidence: 99%